Quality of Earnings and Operating Efficiency of Thai Commercial Bank - Kumpamool, Chamaiporn; Pankhot, Atchimaporn; Chancharat, Surachai (KKBS Journal of Business Administration and Accountancy, 2020)
This study is aimed to analyze Quality of Earnings (QE) and Operating Efficiency (OE) of 13 Thai Commercial Banks. Data were collected from annual performance summary reports for a decade since 2008 through 2017. Those data are statement of financial position, income statement, statement of cash flow, and note to financial statement. Other sources of data are books, journals, e-journals, which revealed to the public published. Financial ratio is used to analyze include statement of cash flow and consolidate financial statement for QE and OE using statistical program to investigate correlation coefficient between QE and OE. The result found that most of commercial banks got the positive figures of the average of QE and OE. It explicitly indicates that the status of earning is in good criteria and good operating efficiency. Both of QE and OE are relate together in same direction with very low positive correlation coefficient. There are 2 prediction variables, the ratio of operating efficient to current liabilities and the ratio of cash flow to revenue interest and dividend, are significantly correlates at the level of 005. It explicitly indicates that quality earning reflects by the operating efficiency. The operation efficiency increasing reflects the amount of earnings, that is a quality earning